A Review Article on dose of Matra Basti - Bhoi, Snehalata; Hakkandi, Suresh N; Akki, Manjunath (International Research Journal of Ayurveda & Yoga, 2022)
Panchakarma presents a unique approach of Ayurveda with specially designed five procedure of internal purification of the body through the nearest possible route. These are Vamana, Virechana, Basti, Nasya and Raktamokshana. Ayurveda considers Basti Chikitsa to be one of the most important Panchakarma treatment. The therapeutic oil or herbal decoction is administered through the anal route in Basti Karma. Matra Basti is one among the Sneha Basti. It is termed so because the dose of Sneha used in it is small when compared to the dose of Sneha Basti. Matra Basti that, there is no restriction of food or regimen while administering Matra Basti. It can be administered continuously in all seasons. The term Matra Basti is popular because of its dose only, because Sneha is administered in the Hraswamatra. Here this article has made to know the different dose of Matra Basti as per different Achaya.